Galleria mellonella for the Evaluation of Antifungal Efficacy against Medically Important Fungi, a Narrative Review - Jemel, Sana (Microorganisms, 2020)
The treatment of invasive fungal infections remains challenging and the emergence of new fungal pathogens as well as the development of resistance to the main antifungal drugs highlight the need for novel therapeutic strategies. Although in vitro antifungal susceptibility testing has come of age, the proper evaluation of therapeutic efficacy of current or new antifungals is dependent on the use of animal models. Mammalian models, particularly using rodents, are the cornerstone for evaluation of antifungal efficacy, but are limited by increased costs and ethical considerations. To circumvent these limitations, alternative invertebrate models, such as Galleria mellonella, have been developed. Larvae of G. mellonella have been widely used for testing virulence of fungi and more recently have proven useful for evaluation of antifungal efficacy. This model is suitable for infection by different fungal pathogens including yeasts (Candida, Cryptococcus, Trichosporon) and filamentous fungi (Aspergillus, Mucorales). Antifungal efficacy may be easily estimated by fungal burden or mortality rate in infected and treated larvae. The aim of the present review is to summarize the actual data about the use of G. mellonella for testing the in vivo efficacy of licensed antifungal drugs, new drugs, and combination therapies.